Parametric Value at Risk models for hedge fund application - Micallef, Pierre (2008)
Recent events over the last year with regards to the US sub-prime crisis and the collapse of three major hedge funds, Bear Stearns, UBS's- Dillon Read Capital Management and Focus Capital, have highlighted that it is a common misconception within finance that extreme events have negligible probability.